Tlingit totem pole in front of abandoned house, Tuxekan, Alaska, ca. 1923 - Thwaites, John E.
Ca. 1920-1925 Caption on image: Thwaites. 5869. Totem at abandoned village. Alaska Notes from unidentified sources: Tuxekan